(untitled) (Research, Society and Development, 2022)
The objective of this research is to carry out a review protocol to map the Educational Actions for Family Members of People with Borderline Personality Disorder. It is a research protocol based on the Joanna Briggs Institute (JBI) manual, following the checklist of the Prefered Reporing Items for Systematic Review and Meta-Analyses - Extension for Scoping Reviews (PRISMA-ScR). Search and data collection will be carried out in October 2021 with the descriptors of Health Science (DeCS) and Medical Subject Headings (MeSH). The selection of studies will be made by two researchers independently. For the interpretation of the results, the IRaMuTeQ software will be used, followed by the analysis of similarity and word cloud and the textual corpus based on thematic analysis.